A supramolecular hydrogel self-assembled from pentafluorobenzyl-dipeptide1. Issue 41 (7th May 2015) - Hsu, Shu-Min; Chang, Jui-Wen; Wu, Fang-Yi; Lin, Yu-Chun; Lai, Tsung-Sheng; Cheng, Hsun; Lin, Hsin-Chieh
<x xml:space="preserve">Abstract</x> We report a new aromatic-capped peptide amphiphile which is able to form a supramolecular hydrogel under neutral pH.